Kreativitas dalam Bingkai Arab: Ketegangan antara Standarisasi Akademik dan Pengembangan Fitrah dalam Pendidikan Islam - Ridwan Hidayat; Nadia Fauziah; Risti Risti; M. Djaswidi Al-Hamdani; Soni Samsul Rizal (An-Nuha, 2026)
Islamic education aims to develop human beings holistically through the integration of intellect, moral conduct (adab), and creativity; however, modern educational practices often reveal tensions between academic standardization and the development of students’ creative thinking, where creativity is frequently perceived as a deviation from academic compliance. This study employs a qualitative approach using a literature review of classical and contemporary sources related to Islamic education, creativity, adab, Sharia, and the concept of Insan Kamil. The findings indicate that the Islamic educational trilogy: tarbiyah, ta’lim, and ta’dib, positions creativity as a legitimate expression of intellect and a form of intellectual worship when guided by adab and Sharia values. Academic standardization plays an important role in ensuring educational quality, yet rigid implementation may constrain originality and individual potential. Sharia functions as an ethical framework that directs creative freedom to remain aligned with human fitrah and moral responsibility. The integration of adab and creativity has significant implications for shaping the profile of Insan Kamil, characterized by intellectual excellence as well as spiritual, social, and ethical maturity; therefore, the reconstruction of contemporary Islamic education should place creativity within the framework of adab to remain relevant in the era of globalization while preserving its Islamic identity